Hagiography and the Tijaniyah Order of Shaikh Badruzzaman in Garut, West Java, 1990-1935 - Nuraidah, Syifa; Hidayat, Asep Achmad; Supendi, Usman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Shaykh Badruzzaman is a figure of great influence who teaches the Tijaniyah Order in Garut. Syaikh Badruzzaman's specialty or Karomah was already visible when he was born until the colonial period. His journey in studying which made Syaikh Badruzzaman explore knowledge from various teachers, so that he had rejected the teachings of the Tijaniyah order at first and even came to the leaders of the Tijaniyah order to discuss. This is interesting, where he initially rejected and finally accepted and even received an Ijazah and spread the Tijaniyah order in Garut. The purpose of this research is to find out that there is Karomah what is in Syaikhuna Badruzzaman that appears since he was born, then how his thoughts in accepting and developing the teachings of the Tijaniyah tarekat. In this research, the methods used are the stages of heuristics, criticism, interpretation and historical historiography. The results of this study show that Syaikh Badruzzaman has several Karomahs, among others, when he was born, a very large light beam appeared, when reciting the Al-Quran he always slept, but when asked, he could explain in detail and correctly, when the lights went out in the pesantren when the students were reciting the Koran, there was light from Syaikh Badruzzaman's body, and other karomahs. In the teachings of the Tijaniyah tariqah he refused, but after a while he changed without knowing why, then hesitated, then accepted it and came to Shaykh Ali bin Abdullah At-Thayyib and then spread it.